Penerapan Teknologi Informasi pada Pelayanan Pengurusan Paspor di Kantor Imigrasi Kelas II TPI Tanjung Balai Karimun - Dewi Asrianingsih; Agus Hendrayady; Okparizan Okparizan (Universitas Katolik Widya Karya Malang, 2023)
The study is based on the problems that occurred in passport management at the immigration office of class ii before the release of the apapo and m-passport applications, and the supervision and services that passport care applicants face such as less effective assurance of service, inefficient institutional performance efficiency, queue issues at the slow service bureau, People had to wait a long time to manage passports, but sometimes it was also unclear that their services, once applied online, still lacked the requirement of service to manage passports and were unable to schedule the days and times. Immigration office class II TPI Tanjung Balai Karimun applies to information technologies based on applications systems and some service innovations such as friendly ham, eazy passport, sicross and sijamat are a step to make it easier in the process of better passport management management. The study aims to know the effect after information technology has been applied to passport management services and to use a qualitative approach or type of descriptive with the paradigm used is constructivism, which suggests that knowledge is not only the construct of subject thought studied and related to this study of the subjective and subjective realities rather than the product of experience alone, But it is a construct by thinking with the application of applications for information technology service. The theory used by the sangkala (2013) analysed is five major indicators or strategies of innovation in the government sector: integrated services, decentralized services and monitoring services, joint operation, citizen outreach, and the introduction of communication and information technology. Instruments of data gathering that are interviews, observations, and documentation and data triangulation. Research shows that the application of information technology to passport management services is so far beyond optimal that the system may have a problem determining schedules because of unstable tissues, it is seen that the service is integrated and based on the soup and brings the ease felt by society.